If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -2c = 31 Solving 9 + -2c = 31 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -2c = 31 + -9 Combine like terms: 9 + -9 = 0 0 + -2c = 31 + -9 -2c = 31 + -9 Combine like terms: 31 + -9 = 22 -2c = 22 Divide each side by '-2'. c = -11 Simplifying c = -11
| M^2-6m-6=-6 | | 11-1/2)t=1/3t-14 | | 2(q-1)=4 | | b/3-13=114 | | M^2-6m-6=6 | | 6(1/4)-3(2/3) | | 2/g | | 2/g | | 28y+8-8=-7 | | 8u-31=-5(2-3u) | | 28y+8-8=-7 | | 28y+8-8=-7 | | 8u-31=-5(2-3u) | | 8u-31=-5(2-3u) | | 28y+8-8=-7 | | 28y+8-8=-7 | | D^2-10d=0 | | -6=8n+1 | | y=2E-05x+0.0048 | | 3/4(x-16)=27 | | -9(t-9)-(t+6)=7 | | 2x+12y=-6 | | 8/x-3/x-1=x/9-7/9 | | -25=14x | | 3/4(x-16=27 | | W^2+8w+72=72 | | W^2+8w+72=0 | | 2/3(c-6)=6 | | x-3=5-3x | | -0.9p-3=0.6 | | z=4x-5y | | t-32=15 |